2017
DOI: 10.1177/0731684417741205
|View full text |Cite
|
Sign up to set email alerts
|

Failure modes and failure mechanisms of single tooth bound to composite pre-tightened tooth connection

Abstract: To assess the failure modes and failure mechanisms of single pre-tightened tooth connection joints, experiments were conducted on the mechanical properties of three different materials―T700/DER-321, T700/EP4221, and E-glass/HCH-8300―under different geometric parameters. During the test, failure processes and details of the fracture surfaces were observed by using a high-speed camera, an optical microscope, and a scanning electron microscope. Then, the failure modes and failure mechanisms of the joints were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The PTST joint involves a stripe-shaped tooth structure grooved at the connection end of the FRP lamina and well-matched teeth on the metal plate connected with the FRP plate (see Figure 1(a)). In this way, certain transverse compressive stresses are exerted onto the FRP tooth plate, further improve the shear strength of composite material, and increase the friction stress on the contact surface; therefore, the PTST joint can have a high ultimate bearing capacity (UBC; Deng et al, 2013;Gao et al, 2018;Liu et al, 2015;Zhao et al, 2015). These studies and applications have shown that the PTST joint can be a viable technique for connecting bridge decks and bridge girders and it has been applied in FRP bridge structures (Yan et al, 2018;Zeng et al, 2019;Zhang et al, 2014Zhang et al, , 2017Zhang et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The PTST joint involves a stripe-shaped tooth structure grooved at the connection end of the FRP lamina and well-matched teeth on the metal plate connected with the FRP plate (see Figure 1(a)). In this way, certain transverse compressive stresses are exerted onto the FRP tooth plate, further improve the shear strength of composite material, and increase the friction stress on the contact surface; therefore, the PTST joint can have a high ultimate bearing capacity (UBC; Deng et al, 2013;Gao et al, 2018;Liu et al, 2015;Zhao et al, 2015). These studies and applications have shown that the PTST joint can be a viable technique for connecting bridge decks and bridge girders and it has been applied in FRP bridge structures (Yan et al, 2018;Zeng et al, 2019;Zhang et al, 2014Zhang et al, , 2017Zhang et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%